The immune response of broiler chickens fed diets supplemented with Propolis and Digestarom under heat stress condition - H., Hasanain shauqi; OMRAN, H. A. (The Iraqi Journal of Veterinary Medicine, 2019)
Summary This research was carried out to evaluate the effect of dietary supplementation of a mixture of propolis and phytogenic (Digestarom)on immune responses against Newcastle disease and infectious bursal disease , also Heterophil/lymphocyte ratios in vaccinated broiler under thermoneutral (maintained on usual heat program)and heat stress maintained in )33 ± 2°C). total of three hundred, one-day-old broilers (Rose 308) chicks were distributed equally in two separated room, thermoneutral groups and heat stress HS groups along the duration of the experiment (42)day, then each group subdivided in to five groups( 30 chicks for each ) as follow: (thermoneutral group and heat stress group )fed a basal diet supplemented with propolis (2g/kg of diet),(thermoneutral group 2and heat stress2)fed Digestarom(150mg/kg).( thermoneutral group 3 and heat stress group 3) fed a mixture of (propolis2g/kg +Digestarom150mg/kg) and two control groups without additive. Antibody titers against Newcastle disease and infectious bursal disease were measured and Heterophil/lymphocyte ratio was estimated. In heat stress chickens the results revealed a significant decrease(P<0.05)in immune response with significant increased(P<0.05) in Heterophil/lymphocyte ratio, while higher significant (P<0.05)in antibody titers with significant decrease (P<0.05) in Heterophil/lymphocyte ratio was showed in all thermoneutral chickens but more significant in thermoneutral group 3 and heat stress group 3 groups were gave the best values in comparing with others groups. The role of Propolis or phytogenic on broiler health and immunity had already been reported, but in this study was reported the effects of their mixture on ameliorating deleterious effects of heat stress.